Um olhar sobre as bruxas de Harry Potter - Medeiros, Rafaela Dantas de [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The main purpose of this capstone project is to demonstrate the complexity of the female characters of Harry Potter's saga, as well as the representativeness of the real women that each carries. For this it will be highlight some female characters that are part of the seven books published and others that appear in only a few passages, because it is believed that they are the ones most worked by the author, J. K. Rowling - those with greater detail of physical characteristics and personality. Besides that, one of these characters, Hermione Granger, will be discussed separately because we believe she is an extremely complex character who carries and conveys the author's thoughts and teachings. This project also presents a relation of data referring to the publications and launches of all the books and films of the saga, besides a brief approach on the narrative structure; in this approach will be presented the position of the series with regard to literary genres, as well as the characteristics responsible for such placement

O presente trabalho tem por objetivo demonstrar a complexidade das personagens femininas que compõem a saga Harry Potter, bem como a representatividade das mulheres reais que cada uma delas carrega. Para isso serão destacadas algumas personagens que fazem parte dos sete livros publicados e outras que aparecem em apenas algumas passagens, por acreditar-se que elas são as mais trabalhadas pela autora J. K. Rowling - aquelas com maior detalhamento de características físicas e de personalidade. Além disso, uma dessas personagens, Hermione Granger, será abordada separadamente, pelo fato de acreditarmos que ela é uma personagem extremamente complexa que carrega e transmite pensamentos e ensinamentos da autora. O trabalho apresenta também uma relação de dados referentes às publicações e lançamentos de todos os livros e filmes da saga, além de uma breve abordagem acerca da estrutura narrativa; nessa abordagem será apresentada a posição da série no que diz respeito aos gêneros literários, bem como as características responsáveis por essa colocação
Keywords: Potter, Harry (Fictitious character); Literatura fantástica; Personagens literários; Mulheres na literatura; Fantasy literature